Redux Quick Start Guide : a Beginner's Guide to Managing App State with Redux. - Lee, James (Packt Publishing Ltd, 2019)
This book will help you get started with the Redux set-up and the Redux ecosystem. You will learn how to integrate Redux with React and other front-end JavaScript frameworks efficiently and manage application states effectively.